2011
DOI: 10.1111/j.1528-1167.2011.03158.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasia type IIb: Completeness of cortical, not subcortical, resection is necessary for seizure freedom

Abstract: SUMMARYPurpose: Focal cortical dysplasia type IIb (FCD IIb) lesions are highly epileptogenic and frequently cause pharmacoresistant epilepsy. Complete surgical resection leads to seizure freedom in most cases. However, the term ''complete'' resection is controversial with regard to the necessity of performing resections of the subcortical zone, which is frequently seen in these lesions on magnetic resonance imaging (MRI). Methods: We retrospectively analyzed 50 epilepsy patients with histologically proven FCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 34 publications
6
58
0
1
Order By: Relevance
“…The surgeon, therefore, aims to resect this subcortical lesion, sometimes as deep as the underlying ventricles. Wagner et al, 26 as described above, already found that such subcortical resection does not correlate with improved seizure control.…”
Section: Volumetrics and Epileptogenesismentioning
confidence: 84%
See 2 more Smart Citations
“…The surgeon, therefore, aims to resect this subcortical lesion, sometimes as deep as the underlying ventricles. Wagner et al, 26 as described above, already found that such subcortical resection does not correlate with improved seizure control.…”
Section: Volumetrics and Epileptogenesismentioning
confidence: 84%
“…Several clinical research groups have studied the impact of different radiological or clinicopathological factors on seizure outcome after extirpative surgery for FCD. [4][5][6][7][8][9][11][12][13][14][15]23,24,26,28,29 Recently, Rowland et al 22 reported on their meta-analysis of predictors of seizure freedom in the surgical management of FCD on the basis of results from 37 selected studies. They noted that complete resection of the anatomical or electrographic abnormality was the most important treatment-related factor predictive of seizure freedom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cause for the increased prevalence in our study is uncertain; however, 3D 1-mm isotropic T2-weighted FLAIR sequences and predominately 3-T images were used and this differs from most prior studies. 6,7,16,22 Interestingly, Wagner et al, 32 in a selected group of 50 predominately adult patients with Type IIb CD (82% lesional), found increased cortical signal in 90% of their patients, 40% of whom underwent 3-T imaging, some with 3D T2-weighted FLAIR sequences. The etiology of this finding is uncertain but may be related to gliosis, cell density, or potentially seizure-related edema.…”
Section: Comparison Of Mri Features and Pathological Findingsmentioning
confidence: 99%
“…A classification of complete resection was given if the entirety of the MRI-documented cortical abnormality was removed. 32 For the purposes of this study, those patients who had functional hemispherotomies and lesional MRI studies with complete resection were considered to have had a complete resection. As this study was not focused on electrophysiology, the relationship of EEG abnormalities and resection was not specifically assessed.…”
Section: Mri Technique and Evaluationmentioning
confidence: 99%